Making Meaning from Historical Fiction Picturebooks about Indonesian Heroes - Parlindungan, Firman; Short, Kathy (International Journal of Multicultural Education, 2024)
We investigated how children make meaning as they read historical fiction picturebooks. Three teachers and a total of 61 students from three different regions of Indonesia participated. We collected field notes, video recordings, and artifacts through read-alouds and subsequent response activities. The findings show that students explored the books by actively engaging in conversations about misconceptions of gender and schooling, connections of the past and the present, and negotiation of moral values and emotions within the fabric of Aceh Province’s history and Indonesian society. It highlights that historical fiction picturebooks can encourage students to think critically about their history and culture to make sense of the world they live in today.